2017
DOI: 10.3390/ijerph14070718
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Dietary Practices in a Mississippi African American Community

Abstract: This study examined the practices, personal motivation, and barriers of African American communities in Mississippi regarding their dietary practices. We selected the Metro Jackson Area comprised of Hinds, Madison and Rankin Counties because it is a combination of urban and rural communities. The sample consisted of 70 participants from seven sites. A total of seven focus groups responded to six questions to assess practices, personal motivation, and barriers to dietary practices: (1) Where in your community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Health professionals, including registered dietitians, should advocate for the inclusion of tree nuts as part of an overall healthy dietary pattern through diet counseling and nutrition education programs. However, it is vital that health professionals are mindful of their clientele’s cultural eating patterns to mitigate challenges to the inclusion of nuts in their clientele’s daily diet [ 70 , 71 ]. Our study showed that usual tree nut intake was greatest among nonHispanic Blacks compared with other races and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals, including registered dietitians, should advocate for the inclusion of tree nuts as part of an overall healthy dietary pattern through diet counseling and nutrition education programs. However, it is vital that health professionals are mindful of their clientele’s cultural eating patterns to mitigate challenges to the inclusion of nuts in their clientele’s daily diet [ 70 , 71 ]. Our study showed that usual tree nut intake was greatest among nonHispanic Blacks compared with other races and ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Increased heathy eating has been associated with reduced risk of obesity and cancer incidence and mortality . One key barrier to healthy lifestyle access is residing in a food desert or food swamp . Food deserts are geographic regions where persons live more than 1.6 km (1 mile) from a supermarket and lack healthy food options.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] One key barrier to healthy lifestyle access is residing in a food desert or food swamp. 16 Food deserts are geographic regions where persons live more than 1.6 km (1 mile) from a supermarket and lack healthy food options. However, food swamps are unique in that these communities are more than 1.6 m (1 mile) from supermarkets and healthy food options and have more proinflammatory food options (eg, corner stores and fast-food restaurants) compared with fresh food options or no options.…”
mentioning
confidence: 99%
“…(Jilcott Pitts et al, 2013;Powell-Wiley et al, 2013). Other social determinants include lower socioeconomic status, which interacts with psychosocial stress, weight stigma, dietary preferences, pressures to conform to food habits, acceptance of larger body size, and hair care practices that limit exercise have also been linked to overweight/obesity (Anekwe et al, 2020;Befort et al, 2008;Bertoni et al, 2011;Hall et al, 2015;Robinson et al, 2012;Thomas et al, 2013;White et al, 2017). Mental illnesses and their treatment may also be a barrier to achieving a healthy weight given their association with dysregulated eating and reduced metabolism (Cortese et al, 2016;Shrivastava and Johnston, 2010;Zimmerman and Wylie-Rosett, 2003).…”
Section: Introductionmentioning
confidence: 99%